2014
DOI: 10.5751/es-06658-190271
|View full text |Cite
|
Sign up to set email alerts
|

Does Pastoralists' Participation in the Management of National Parks in Northern Norway Contribute to Adaptive Governance?

Abstract: ABSTRACT. Norwegian protected areas have historically been managed by central, expertise bureaucracy; however, a governance change in 2010 decentralized and delegated the right to manage protected areas to locally elected politicians and elected Sámi representatives in newly established National Park Boards. We explore how this new governance change affects adaptive capacity within the reindeer industry, as the reindeer herders are now participating with other users in decision-making processes related to larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…Literature on self-organization for the management of common-pool natural resources in general, not restricted to protected areas, consistently finds that the degree of dependence of actors on the resource and their knowledge of protected areas and mental models on conservation are important factors in collective action (Ostrom 1990(Ostrom , 2009Risvoll et al 2014;Delgado-Serrano and Ramos 2015). Zachrisson (2008) supports these results in the case of Norway's neighboring country, Sweden, showing that actors dependent on protected areas favor co-management.…”
Section: H1supporting
confidence: 70%
See 3 more Smart Citations
“…Literature on self-organization for the management of common-pool natural resources in general, not restricted to protected areas, consistently finds that the degree of dependence of actors on the resource and their knowledge of protected areas and mental models on conservation are important factors in collective action (Ostrom 1990(Ostrom , 2009Risvoll et al 2014;Delgado-Serrano and Ramos 2015). Zachrisson (2008) supports these results in the case of Norway's neighboring country, Sweden, showing that actors dependent on protected areas favor co-management.…”
Section: H1supporting
confidence: 70%
“…Often the aim of co-management is to increase the legitimacy of protected areas and moderate negative attitudes toward conservation. Previous literature in the areas of study in this paper has identified tensions between various actor groups resulting in conflict regarding conservation Fedreheim 2013;Risvoll et al 2014Risvoll et al , 2016. These conflicts derive partly from problems of legiti-macy of the protected areas and conflicts between various actor groups.…”
Section: H2mentioning
confidence: 99%
See 2 more Smart Citations
“…Although rare, nonpolitical organizations are sometimes represented in the local boards, such as the Skjåk bygdealmenning (common property) in Breheimen and the Swedish reindeer herders in Øvre Dividalen. In addition, professional advisory committees have been established including local stakeholders such as reindeer herders, landowners, tourism businesses, and recreation interests to provide input to the board (Risvoll et al, 2014).…”
Section: Protected Area Management and Governance In Norwaymentioning
confidence: 99%